2013
DOI: 10.1016/j.amjcard.2012.10.013
|View full text |Cite
|
Sign up to set email alerts
|

Relation of Morbid Obesity and Female Gender to Risk of Procedural Complications in Patients Undergoing Atrial Fibrillation Ablation

Abstract: Obese patients with atrial fibrillation (AF) are frequently managed with AF ablation. We sought to examine whether there exists a body mass index (BMI) threshold beyond which odds of experiencing a complication from AF ablation increase. All patients enrolled in the Vanderbilt AF Registry who underwent catheter-based AF ablation from May 1999 to February 2012 were included. Major complications were recorded. Morbid obesity was defined as BMI >40 kg/m2, and BMI as a continuous variable was examined in multivari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
2
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(43 citation statements)
references
References 21 publications
1
37
2
3
Order By: Relevance
“…Otyłość powiązano również z większą dawką promieniowania i częstością występowania powikłań podczas ablacji AF [302,303]. Warto zauważyć, że poprawa objawowa po przezcewnikowej ablacji AF u otyłych pacjentów wydaje się podobna jak u pacjentów o prawidłowej masie ciała [298].…”
Section: Ablacja Przezcewnikowa U Otyłych Pacjentówunclassified
“…Otyłość powiązano również z większą dawką promieniowania i częstością występowania powikłań podczas ablacji AF [302,303]. Warto zauważyć, że poprawa objawowa po przezcewnikowej ablacji AF u otyłych pacjentów wydaje się podobna jak u pacjentów o prawidłowej masie ciała [298].…”
Section: Ablacja Przezcewnikowa U Otyłych Pacjentówunclassified
“…There is consistency of the data from several studies on the increased procedural risk in women [127,[130][131][132]]. An analysis of 517 AF ablation procedures showed that female gender was an independent predictor of major complications (OR 3.…”
Section: Agementioning
confidence: 96%
“…An analysis of 517 AF ablation procedures showed that female gender was an independent predictor of major complications (OR 3. [132]. For every unit of BMI increment, the probability of complications (mostly vascular) increased by 5% in the entire group, and more than twice (OR 2.23 [95% CI:…”
Section: Agementioning
confidence: 99%
“…Previous data support a higher periprocedural complication rate for patients with obesity undergoing ablation,7 although these results remain elusive. The Atrial Fibrillation Ablation Registry was conducted by the European Heart Rhythm Association (EHRA) of the European Society of Cardiology (ESC).…”
Section: Introductionmentioning
confidence: 99%